Pelaksanaan Tugas dan Wewenang Pemerintah Desa dalam Penyediaan Air Bersih di Desa Lusilame dan Desa Nuba Atalojo Kecamatan Atadei Kabupaten Lembata Ditinjau dari Undang-Undang No 6 Tahun 2014 Tentang Desa - Rosalia Maria Bota; Saryono Yohanes; Hernimus Ratu Udju (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to analyze the implementation of the duties and authorities of the Village Government in the provision of clean water in Lusilame Village and Nuba Atalojo Village, Atadei Sub-district, Lembata Regency as viewed from Law No. 6 of 2014 concerning Villages. The research method used in this research is Empirical research. The location of this research was Lusilame Village and Nuba Atalojo Village, Atadei District, Lembata Regency. The type of data used in this research is qualitative data. The data used in the research based on the relevance of the source data, namely primary data and secondary data. Data collection techniques in this study were carried out by interview, observation, and literature/documentation studies. Data processing techniques in this study include editing, coding, and tabulation. The result of this research is that the implementation of the duties and authority of the Lusilame Village government in implementing development related to the provision of clean water is still less than optimal. As for Nuba Atalojo Village, in carrying out its duties and authorities, the government has tried its best so that the community can be helped by the existence of boreholes even though it is still difficult during the dry season. In terms of Law No. 6/2014 on Villages, the governments of Lusilame Village and Nuba Atalojo Village have also been effective in planning, implementing and monitoring because they include the village community, although only some people have the willingness to be involved. There are 3 main factors that inhibit the duties and authority of the village government in providing clean water, namely, the first is the availability of funds, human resources, and community participation.